Effectiveness of box trainers in laparoscopic training - Dhariwal, Anender Kaur (Medknow Publications, 2007)
RATIONALE AND OBJECTIVES: Various devices are used to aid in the education of laparoscopic skills ranging from simple box trainers to sophisticated virtual reality trainers. Virtual reality system is an advanced and effective training method, however it is yet to be adopted in India due to its cost and the advanced technology required for it. Therefore, box trainers are being used to train laparoscopic skills. Hence this study was undertaken to assess the overall effectiveness of the box-training course. STUDY PROCEDURE: The study was conducted during six-day laparoscopic skills training workshops held during 2006. Twenty five surgeons; age range of 26 to 45 years, of either sex, who had not performed laparoscopic surgery before; attending the workshop were evaluated. Each participant was given a list of tasks to perform before beginning the box-training course on day one and was evaluated quantitatively by rating the successful completion of each test. Evaluation began when the subject placed the first tool into the cannula and ended with task completion. Two evaluation methods used to score the subject, including a global rating scale and a task-specific checklist. After the subject completed all sessions of the workshop, they were asked to perform the same tasks and were evaluated in the same manner. For each task completed by the subjects, the difference in the scores between the second and first runs were calculated and interpreted as an improvement as a percentage of the initial score. STATISTICAL ANALYSIS: Wilcoxon matched-paired signed-ranks test was applied to find out the statistical significance of the results obtained. RESULTS: The mean percentage improvement in scores for both the tasks, using global rating scale, was 44.5% ± 6.930 (Mean ± SD). For task 1, using the global rating scale mean percentage improvement was 49.4% ± 7.948 (Mean ± SD). For task 2, mean percentage improvement using global rating scale was 39.6% ± 10.4 (Mean ± SD). Using Wilcoxon matched-paired signed-ranks test, 2-tailed P-value<0.0001 which is extremely significant. CONCLUSION: This study confirms that a short-term, intensive, focused course does improve laparoscopic skills of trainees. Box-trainers can be used to change the present day didactic training into objective and competency-based. Global rating scale and checklist provide an inexpensive and effective way of objective assessment of performance of laparoscopic skills.